Emergence of a hierarchical brain during infancy reflected by stepwise functional connectivity. Issue 5 (6th March 2017) - Pendl, Suzanne L.; Salzwedel, Andrew P.; Goldman, Barbara D.; Barrett, Lisa F.; Lin, Weili; Gilmore, John H.; Gao, Wei
Abstract: The hierarchical nature of the brain's functional organization has long been recognized, but when and how this architecture emerges during development remains largely unknown. Here the development of the brain's hierarchical organization was characterized using a modified stepwise functional connectivity approach based on resting‐state fMRI in a fully longitudinal sample of infants ( N = 28, with scans after birth, and at 1 and 2 years) and adults. Results obtained by placing seeds in early sensory cortices revealed novel hierarchical patterns of adult brain organization ultimately converging in limbic, paralimbic, basal ganglia, and frontoparietal brain regions. These findings are remarkably consistent with predictive coding accounts of neural processing that place these regions at the top of predictive coding hierarchies. Infants gradually developed toward this architecture in a region‐ and step‐dependent manner, and displayed many of the same regions as adults in top hierarchical positions, starting from 1 year of age. The findings further revealed patterns of inter‐sensory connectivity likely reflecting the emergence and development of multisensory processing strategies during infancy, the strengths of which were correlated with early cognitive development scores. Hum Brain Mapp 38:2666–2682, 2017 . ©2017 Wiley Periodicals, Inc.